Efektivitas Penggunaan Aplikasi TikTok dalam Pembelajaran Maharah Kalam di Universitas Islam Tribakti Lirboyo Kediri - Rifa'i, Arwan (JOM, 2025)
This study investigated the effectiveness of TikTok as an instructional medium for developing maharah kalām (oral proficiency) in Arabic language acquisition among students at the Islamic University of Tribakti Lirboyo, Kediri. Using an experimental pre-test–post-test design, the research assessed improvements in students’ oral competence after TikTok integration as a pedagogical tool. Findings revealed a statistically significant positive impact on Arabic oral proficiency: the calculated t-value of 8.32 exceeded the critical t-value of 2.01 at the 0.05 significance level. Students’ mean scores improved from 62.35 to 81.47. Substantial progress occurred across oral proficiency subcomponents: fluency (61.2-82.5), grammatical accuracy (58.7-76.8), lexical appropriateness (65.3-84.2), and pronunciation (63.8-79.3). Student engagement also increased, with active participation rising from 45% to 87% and average speaking duration per session extending from 2.3 to 5.7 minutes, reflecting greater confidence and sustained communicative performance. These results highlight TikTok’s potential as an innovative and effective platform for enhancing Arabic oral proficiency.